Teachers Readiness Training in Implementing the Independent Curriculum (Concept Understanding, Structure, Learning Approach): Concept Understanding, Structure, Learning Approach - Tri Yuni Hendrowati; M. Badrun; Siswoyo (Journal of Society, Community and Business Development, 2024)
The teachers readiness training in implementing the Independent Curriculum is designed to increase their understanding about the concept, structure, and learning approach in the Independence curriculum. The Independent curriculum offers the approach that more focuses on skill development and understanding rather than factual knowledge. This training is conducted through various methods such as lecturing, group discussion, case study, and learning simulation. The teachers will be actively involved in learning process so that they can understand and internalize the concept and their taught skills. Besides, there will be reflection section and feedback to help the teachers in repairing and increasing their learning practice. By the increasing of the teachers understanding and skill in implementing the Independent Curriculum, it is hoped that there will be the increasing of learning quality in the class. This training is one of the first steps in succeeding the implementation of Independent Curriculum as a whole in the school level. Keywords: Independent Learning, teacher readiness, curriculum concept, curriculum structure, Learning Approach